Producing knowledge in times of health crises - Paul Forster; Olivier Charnoz (Revue d'anthropologie des connaissances)
Examining efforts to control avian influenza in Indonesia between 2005 and 2010, this article investigates why the internationally funded and designed response initially focused so much on community level “backyard” poultry farming, thus excluding, or excusing, a large and poorly regulated industrial sector from involvement in responding to disease spread and persistence. A range of biases acting on national and international agencies are identified that contributed to distorted production of knowledge and led to a focus on small farmers instead of all relevant stakeholders. These include too rapid acceptance of the intrinsic “biosafety” of industrial poultry production, a “pro-poor” development stance, the unwillingness of public and private sectors to co-ordinate, and a human rather than animal health framing. These biases were reinforced by the organisational arrangements and incentives within donor and implementing organisations. If global health emergencies are to be more effectively addressed, global and national health governance routines must better acknowledge how knowledge is produced and used in times of crisis.